2015
DOI: 10.1016/j.jare.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Laser researches on livestock semen and oocytes: A brief review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
(76 reference statements)
0
13
0
2
Order By: Relevance
“…The effect of laser irradiation of sperm depends on emission wavelength and the laser energy density encountering the sample. Irradiation procedures therefore need to consider output power of lasers, the use of continuous laser wave or pulse modes, the laser distance to cells and transmission rate of the laser light through plastic surrounding the sample (Abdel‐Salam & Harith, ; Corral‐Baqués, Rivera, Rigau, Rodríguez‐Gil, & Rigau, ). A recent study shows that short‐term (3 min) exposure of semen droplets on objective glass to LED light of different wavelengths with total power densities between 2.16 and 8.23 mW/cm 2 slightly stimulates sperm motility in asthenozoospermic men (Ban Frangez, Frangez, Verdenik, Jansa, & Virant Klun, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of laser irradiation of sperm depends on emission wavelength and the laser energy density encountering the sample. Irradiation procedures therefore need to consider output power of lasers, the use of continuous laser wave or pulse modes, the laser distance to cells and transmission rate of the laser light through plastic surrounding the sample (Abdel‐Salam & Harith, ; Corral‐Baqués, Rivera, Rigau, Rodríguez‐Gil, & Rigau, ). A recent study shows that short‐term (3 min) exposure of semen droplets on objective glass to LED light of different wavelengths with total power densities between 2.16 and 8.23 mW/cm 2 slightly stimulates sperm motility in asthenozoospermic men (Ban Frangez, Frangez, Verdenik, Jansa, & Virant Klun, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that red light irradiation of sperm with different laser sources improves motility and mitochondria function (Abdel‐Salam & Harith, ; Preece et al., ). Light‐emitting diodes (LED) can be effective alternative light sources, providing advantages such as broad beam width and cost‐efficiency (Rohringer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that the mechanisms involved in laser interaction with cells are due to photon absorption by cellular photoreceptors that trigger chemical reactions such as glycolysis and oxidative phosphorylation. This could accelerate RNA transcription and DNA replication (Abdel-Salam et al 2015). LLLI is an efficient tool to modulate the granulosa cells and oocyte metabolism (Soares et al 20104).…”
Section: Discussionmentioning
confidence: 99%
“…Многочисленные исследования под-тверждают положительное влияние НИЛИ на спер-матозоиды различных животных, увеличивается их подвижность и содержание аденозинтрифос-фата (АТФ) [33][34][35][36][37][38][39][40][41], повышается продолжитель-ность жизни клеток и вероятность оплодотворе-ния. Именно повышение концентрации Ca 2+ , в том числе вызванное лазерным освечиванием, стиму-лирует работу митохондрий и синтез АТФ [31], что играет ключевую роль в обеспечении подвижности сперматозоидов.…”
Section: экспериментальные исследованияunclassified
“…Лазерная стимуляция является более эффек-тивной и менее затратной технологией, которая может быть использована на достаточно хорошей научной основе для совершенствования искус-ственного осеменения и эффективности эмбрио-нальных систем [33]. В результате лазерного освечивания in vitro повышается качество спер-мы быков, кроликов и птицы, используемой после длительного хранения в замороженном состоянии: увеличивается проникающая способность сперма-тозоидов (капацитация), индуцируется их акро-сомная реакция при снижении процента погибших клеток [38,[47][48][49].…”
unclassified